UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA DENGAN METODE TUTOR SEBAYA PADA MATERI MATRIKS - Darmawati Darmawati (UNIVERSITAS TANJUNGPURA, 2020)
The purpose of this study was to improve the activities and learning outcomes of students of class XI MIA 3 in SMA Negeri 1 Sekadau in the academic year 2019/2020 on matrix material using peer tutoring methods. This type of research is a classroom action research carried out in 2 cycles, each cycle consisting of 4 stages of planning, action implementation, observation and reflection. Retrieval of data through a collection using a collection of observations and learning outcomes are obtained by providing a final test at the end of each cycle. The results of observations for student activity during pre-cycle 67.81% in the first cycle to 76.88% and in the second cycle to 86.46% means that there is an increase of 17.82%. Mathematical learning outcomes from the first cycle increased by 41.00%, while from the first cycle to the second cycle increased by 14.46%. So it can be removed by using the peer tutoring method to increase the activity and learning outcomes of students of class XI MIA 3 of SMA Negeri 1 Sekadau in the academic year 2019/2020 on matrix material.Keywords: activities, learning outcomes of peer tutoring methods, matrix